Parting Ways Too Soon: Arendt contra Butler on Zionism. Issue 3 (2nd April 2020) - Lederman, Shmuel
ABSTRACT: In this article, I discuss the way Judith Butler builds on Hannah Arendt's political thought for her critique of Zionism. While her critique is valuable in many ways, I argue that it also obscures the complexity of Arendt's position on Zionism. Instead of Butler's portrayal of Arendt as a proto-anti-Zionist, along the lines of Butler herself, I suggest that Arendt was a radical Zionist. Arendt, I contend, offered a radical critique of Zionism but at the same time she supported the establishment of a national home for Jews in Palestine, without losing sight of the different streams within Zionism or the different paths that were possible at every juncture in the years leading to the foundation of the state. By contextualizing Arendt's position on Zionism against the background of her broader political thought, I attempt to show that, while her engagement with the Zionist movement largely ceased in the late 1940s, her support of Zionism continued to inform her major writings, from her recognition of the need of individuals to belong to a national community to her emphasis on the artificiality of any collective achievement. Through this reconstruction of Arendt's views of Zionism I attempt to show that she provides us with important sources for engaging with Zionism in a critical way without dismissing and rejecting it, as Butler and other progressives do, as a settler-colonialist enterprise.